The requirements of activating the role of Educational research in Achieving the knowledge society from the view point of Faculty members in the Faculty of Education at Damascus University (Damascus University Journal of educational and Psychologyical sciences, 2021)
The purpose of this research is to define the requirements of activating the role of educational research in achieving the knowledge society from the point of view of the faculty members in the Faculty of Education at Damascus University. This is achieved by defining the requirements of activating the role of educational research in the acquisition, production and application of educational knowledge as well as defining the effect of the independent variables (gender, degree and practical experience) on the responses of sample members, which included (52) members of the teaching staff at the Faculty of Education at the University of Damascus. To achieve this objective, the researcher used the descriptive analytical approach and prepared a questionnaire that included (39) items distributed to three axes and the results of the research showed that the value of the arithmetical mean of the responses of the sample members of the study sample to the complete questionnaires was (168,9038), indicating the great importance of these axes in determining the research objective and None of the independent variables of the research affect respondents' responses, then the research presented several recommendations, the most important of which are: The necessity of enabling educational researchers to use the skills of educational statistics and the use of various statistical programs, develop their skills in dealing with the different sources of knowledge contained in paper and electronic libraries and the need of taking benefit from the applications of information technology in facilitating the dissemination of educational knowledge, receiving research ideas and turn them into integrated research projects and encourage researchers and faculty members to carry out research that characterizes the efficiency of educational systems and develop them to meet the requirements of the knowledge society and to conduct further future studies and organize conferences, seminars and workshops to educate the educational community at all levels of the importance of the role of educational research in the realization of the knowledge society.
Keywords: Educational Research, Knowledge Society.